A Crystalline Imine-Linked 3-D Porous Covalent Organic Framework - Uribe-Romo, Fernando J; Hunt, Joseph R; Furukawa, Hiroyasu; Klöck, Cornelius; O’Keeffe, Michael; Yaghi, Omar M (Journal of the American Chemical Society, 2009)
A new crystalline porous three-dimensional covalent organic framework, termed COF-300, has been synthesized and structurally characterized. Tetrahedral tetra-(4-anilyl)-methane and linear terephthaldehyde building blocks were condensed to form imine linkages in a material whose X-ray crystal structure shows five independent diamond frameworks. Despite the interpenetration, the structure has pores of 7.2 Å diameter. Thus, COF-300 shows thermal stability up to 490 °C and permanent porosity with a surface area of 1360 m2 g−1.